2001
DOI: 10.1093/cercor/11.10.975
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Architecture Distinguishes Prefrontal Cortical Systems in the Rhesus Monkey

Abstract: The prefrontal cortex encompasses a large and heterogeneous set of areas, whose borders have been variously mapped in different architectonic studies. Differences in cortical maps present a formidable problem in comparing data across studies and in constructing databanks on the connections and functional attributes of cortical areas. Here we used quantitative approaches to cortical mapping to investigate (i) if architectonic areas of the prefrontal cortex in adult rhesus monkeys have unique profiles and (ii) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

41
319
6
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(368 citation statements)
references
References 102 publications
41
319
6
2
Order By: Relevance
“…The terminology for the architectonic areas of the prefrontal cortices was based on the map of Barbas and Pandya (Barbas and Pandya, 1989), and the quantitative architecture of prefrontal cortices (Dombrowski et al, 2001). Borders of prefrontal architectonic areas and their layers were delineated in the same sections counterstained with thionin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The terminology for the architectonic areas of the prefrontal cortices was based on the map of Barbas and Pandya (Barbas and Pandya, 1989), and the quantitative architecture of prefrontal cortices (Dombrowski et al, 2001). Borders of prefrontal architectonic areas and their layers were delineated in the same sections counterstained with thionin.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the relative laminar distribution of connections linking pairs of prefrontal cortices is highly correlated with the relationship of the areas' structure (Barbas and Rempel-Clower, 1997). The structure of different cortical areas is assessed quantitatively by the number of identifiable layers or overall neuronal density (Dombrowski et al, 2001;Medalla and Barbas, 2006). According to the structural model, 'feedforward' connections originate from a type of cortex with more layers or higher cell density than the cortex of destination and 'feedback' connections reflect the opposite relationship.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These IL-1 family inflammatory mediators show cell-specific patterns of production, expression and release since ligands are made principally by glia (and some neurons) while astrocytes and neurons express the signal transducing IL-1 receptor, IL-1RI (Ban et al, 1991(Ban et al, , 1993Fontana et al, 1982;Giulian et al, 1986;Lechan et al, 1990). In addition, neurons (and glia) can be differentially distributed between and within various brain regions (Dombrowski et al, 2001). Thus to most accurately characterize the net effects of IL-1 on brain function, not only should simultaneous measurements be made of six key IL-1 family cytokine proteins, but they should be made from sample volumes small enough to account for potential regional variations of the related variables.…”
Section: Introductionmentioning
confidence: 99%